ANALISIS KINERJA KEUANGAN BANK UMUM KONVENSIONAL DENGAN ASET TERENDAH DI INDONESIA PERIODE 2014-2017 - Jefri Thomi da Costa Boreel; Mintarti Ariani; Bambang Budiarto (Jurnal Ekonomi dan Bisnis, 2018)
This research aims to analyze the payback or Return on Assets (ROA) which has very significant effect against the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Net Performing Loan (NPL), Net Interest Margin (NIM), and operatingexpenses against the operating income (BOPO). This research uses population of 13 commercial banks with the lowest accounting assets in Indonesia for 2014-2017 period. In this research, the secondary data is taken in the form of the financialstatements of the bank starting from 2014 until 2017. Technique of data analysis in this study uses regression analysis panel where Return on Asset (ROA) as its dependent variabel and the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Net Performing Loan (NPL), Net Interest Margin (NIM), and operating expenses against operating income (BOPO) as its independent variabel. The results of this research provide evidence that Net Performing Loan (NPL), Net Interest Margin (NIM), and operating expenses against the operating income (BOPO) partially have significant influence towards Return on Asset (ROA) on 13 commercial banks, while Loan to Deposit Ratio (LDR), and the Capital Adequacy Ratio (CAR) partially do not havesignificant influence towards Return on Asset (ROA).